If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 = 8k Solving 24 = 8k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-8k' to each side of the equation. 24 + -8k = 8k + -8k Combine like terms: 8k + -8k = 0 24 + -8k = 0 Add '-24' to each side of the equation. 24 + -24 + -8k = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -8k = 0 + -24 -8k = 0 + -24 Combine like terms: 0 + -24 = -24 -8k = -24 Divide each side by '-8'. k = 3 Simplifying k = 3
| 8-6(2x+2)=9(3x+4)+7 | | x/2(-6)=6 | | -4u+7=4u+7 | | 2x+x-6=3 | | 7(3x-5)=3(x+3)-17 | | m^4-625= | | 34.2/7 | | -0.2w-1.7=-1.1w-0.8 | | x+(24/x)=10 | | 2x^2-14x=-20 | | 7/2/1/2 | | 0.3(z-1.5)=1.1(z+0.5) | | -(9y-1)=-9y+17 | | 4/3/8/9 | | -z+7=-3 | | 4y^2-32y=0 | | (6-4)6+4= | | 3y*2-(7+2y*2)-4y+(y+9)= | | -3y-3=3y+5 | | 3y-3=3y+5 | | 11t=121 | | 10x-4x+3=3(x+6) | | -3y-3=-3y+5 | | 2x-1.9=-0.25x+2.37 | | k^5+4k^4-32k^3= | | -42/3=2a/3+1/3+a/3 | | 12y+4=0 | | (x-6)(x+8)=-3(x-14) | | 427/7 | | 9t+7=-9t-11 | | -4t+9=-10 | | 3x^2+23=74 |